2021
DOI: 10.3390/jof7100790
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Chronic Pulmonary Aspergillosis in Africa

Abstract: Africa has a high burden of tuberculosis, which is the most important risk factor for chronic pulmonary aspergillosis (CPA). Our goal was to systematically evaluate the burden of CPA in Africa and map it by country. We conducted an extensive literature search for publications on CPA in Africa using the online databases. We reviewed a total of 41 studies published between 1976 and 2021, including a total of 1247 CPA cases from 14 African countries. Most of the cases came from Morocco (n = 764, 62.3%), followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Chronic pulmonary aspergillosis is a pulmonary infection caused by caused by Aspergillus species [ 1 ]. Recent reports have shown an increased incidence of CPA in recent years [ 2 4 ]. The European Society for Clinical Microbiology and Infectious Diseases (ESCMID) and the European Respiratory Society (ERS) reached an agreement on the rationale and clinical guidelines for diagnosis and management for CPA in 2015 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pulmonary aspergillosis is a pulmonary infection caused by caused by Aspergillus species [ 1 ]. Recent reports have shown an increased incidence of CPA in recent years [ 2 4 ]. The European Society for Clinical Microbiology and Infectious Diseases (ESCMID) and the European Respiratory Society (ERS) reached an agreement on the rationale and clinical guidelines for diagnosis and management for CPA in 2015 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study evaluating over 1200 cases of CPA in Africa identified current active or previous PTB as an underlying structural lung disease in over 70% of the cases 16 . A few epidemiological studies from across Africa and other countries in Asia have reported varying CPA prevalence based on the population of TB patients studied.…”
Section: Discussionmentioning
confidence: 99%
“…Rare cases of CPA misdiagnosed as pulmonary tuberculosis and pneumonia have been reported in immunocompetent and immunodeficient children with chronic granulomatous disease and hyper-IgE syndrome [ [10] , [11] , [12] ]. Untreated CPA in patients with respiratory disease can be life-threatening, leading to significant deterioration in their quality of life with a case fatality of 75–80% in 5 years [ 13 ]. In Africa, the availability and access to essential diagnostics and medications for most fungal diseases remain a challenge [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Untreated CPA in patients with respiratory disease can be life-threatening, leading to significant deterioration in their quality of life with a case fatality of 75–80% in 5 years [ 13 ]. In Africa, the availability and access to essential diagnostics and medications for most fungal diseases remain a challenge [ 13 ]. The majority of CPA in Nigeria are in the adult population with sparse data on the paediatric population.…”
Section: Introductionmentioning
confidence: 99%